Bis(3-Ammoniopropyl)Ethylenediaminium Bis(Squarate) - Paşaoĝlu, H.; Yuan, O.O. (Int Union Crystallography, 2006)
In the crystal structure of the title compound, C8H 26N44+·-2C4O4 2-, the bis(3-ammoniopropyl)ethylenediaminium (PAED) cation lies on an inversion centre and the squarate anion (Sq2-) is in a general position. Salt formation occurs by donation of four H atoms from two squaric acid molecules to the bis(3-aminopropyl)ethylenediamine base. In the crystal structure, the strongest interactions are between H atoms of NH2 + groups and squarate O atoms. All the H atoms of NH3 + groups of the PAED cation also participate in hydrogen bonding with the O atoms of the Sq2- anion, contributing to the crystal packing. © 2006 International Union of Crystallography All rights reserved.